SURVEI SURVEILANS PERILAKUBERISIKO TERTULAR HIVPADA REMAJA JALANAN TAHUN 2011 - Wahjudi, Pudjo; Prasetyowati, Irma; Ariyanto, Yunus (IKESMA, 2012)
At present, the world have a pandemikHIV. No one country in the world free from this infection, including Indonesia. In Indonesia, the infection has been alarming stage. If nothings done to prevent and control the spread of HIV, the next ten years, HIV infection such as sub sahara-africa, where there will be 3 of 10 people infected HIV. The Human Immunodeficiency Virus (HIV) is a type of virus called a retrovirus and it is spreadingÂ  throughout the world include sexual contact, sharing needles, and by transmission from infected mothers to their newborns during pregnancy, labor, or breastfeeding. Purpose of this study was determine HIV risk behaviors in youth on the street in Jember district. Behavioral surveillance survey aims to monitor changes in sexual behavior and injecting risk from time to time. Target Population of Behavioral surveillance stratified by contributing to the HIV epidemic, one of which is youth aged 15 -24 years old, men and women, educated or not. This is descriptive approach with survey methods to 50 youths. The result were contained two behavioral surveillance of key indicators that have high percentage. There were heard HIV and AIDS(87,8%) and knowing to prevent HIV and AIDS using condom(98%). The recommendation is that the youth should have healthy behavior, alert to the HIV and AIDS, no sex before marriage and avoid other risky behaviors.